Implementasi Kebijakan Kabupaten Layak Anak Di Kabupaten Probolinggo - Mamluatun Ni’mah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Probolinggo has done the policy of planning worthy children regency. It can be said that Probolinggo has just step up to do that policy. The purpose of the research is to describe the implementation of planning worthy children regency in Probolinggo and to know the factors that support and embedded the success of the policy. The research used qualitative approach by descriptive research. The result of the research showed that the implementation of worthy children policy used Darwin theory by doing 3 steps: interpreting, organizing and applying. The factors that supports its success is the commitment of departments and the leader in fulfilling the facilities and budgeting, although the ego-sectoral of departments were still exist. This could slow up the coordination and the success of KLA. In sort, it needs more intentional coordination and the same commitment and paradigm from the regency to rural level.